On the Modular Specification of NFPs: A Case Study - Moreno-Delgado, Antonio; Troya-Castilla, Javier; Durán-Muñoz, Francisco Javier; Vallecillo-Moreno, Antonio Jesús (Jornadas de Ingeniería del Software y Bases de Datos, 2013)
The modular specification of non-functional properties of systems is a current challenge of Software Engineering, for which no clear solution exists. However, in the case of Domain-Specific Languages some successful proposals are starting to emerge, combining model-driven techniques with aspect-weaving mechanisms. In this paper we show one of these approaches in practice, and present the implementation we have developed to fully support it. We apply our approach for the specification and monitoring of non-functional properties using observers to a case study, illustrating how generic observers defining non-functional properties can be defined in an independent manner. Then, correspondences between these observers and the domain-specific model of the system can be established, and then weaved into a unified system specification using ATL model transformation. Such a unified specification can also be analyzed in a natural way to obtain the required non-functional properties of the system.
Keywords: Informática; Soporte lógico; Non-functional properties; Domain-specific languages; Model transformations; Weaving mechanisms